If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -29 + 10x = 9 Reorder the terms: -29 + -8x + 10x = 9 Combine like terms: -8x + 10x = 2x -29 + 2x = 9 Solving -29 + 2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 2x = 9 + 29 Combine like terms: -29 + 29 = 0 0 + 2x = 9 + 29 2x = 9 + 29 Combine like terms: 9 + 29 = 38 2x = 38 Divide each side by '2'. x = 19 Simplifying x = 19
| f(x)=4e^3x+2 | | 2sinx-6=0 | | -28+2n=4(6n-7) | | 5h^2+400=0 | | 6y=7+5y | | X^2-8*x+7=0 | | 3x-5x=23-15 | | 13-4x-7x=18x+14 | | m^6=16m^4 | | 3(x-4)2=3(x-1)-7 | | 32x+5=3x-3 | | 7-3x=2x+27 | | pH=-log[5.7*10(-4)] | | 11x-85+x=167 | | 2(8x+60)=5(9x-10) | | 12x-3x-17=-12x+27 | | 7-3x=2+27 | | -10(-3-9m)=-5(11m-6) | | 2(2+b)+(2b)=900 | | 5x^2-23z+12=0 | | 4-9=4x | | 5y+9wheny=6 | | 0=15m^2-10m-25 | | 1.10=2x+1 | | 2(y-3)=34 | | 4-8=4x-1 | | y=15m^2-10m-25 | | -12r^2+4=13r | | in(8x)=5.5 | | 3(5-2)=y | | -81-6x=-18+3x | | (5z+6)(3-z)=0 |